First record of the genus and species Zefevazia peruana (Boucomont, 1902) (Coleoptera: Bolboceratidae: Bolboceratinae) from Ecuador - Clavijo-Bustos, Julián (2022)
The first report of the genus and species Zefevazia peruana (Boucomont, 1902) for Ecuador is presented. The species is previously known only from a few localities in northern Peru, and is now also recorded from Santa Elena, southern Ecuador. This report represents the northernmost record of the genus and species.